Strong Red, Blue, and Yellow Emissions from Eu3+ and Dy3+-Doped CaF2 Nanocrystals - Sarkar, S. (Journal of Scientific Research, 2024)
This paper represents a simplistic hydrothermal method for the synthesis of lanthanide (Ln3+)-doped (Ln= Eu, Dy) alkaline earth metal fluoride, i.e., CaF2 nanocrystals coated with poly(acrylic acid) (PAA). The structural and optical characterization of as-prepared nanocrystals is performed using scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), Fourier transform infrared spectrum (FTIR), thermogravimetric analysis (TGA), photoluminescence spectroscopy (PL), and PL lifetime measurements. It is observed that CaF2 exhibits strong red emission when doped with Eu3+ (5 mol%) ions, whereas it shows strong blue and yellow emission when doped with Dy3+ (2 mol%) ions. PAA coating helps to enhance the stability as well as water dispersibility of the nanocrystals. Moreover, this method can be extended to make other lanthanide-doped alkaline earth metal fluoride nanocrystals. The high photoluminescence efficiency and water solubility of the nanocrystals make the material to be used in many fields of optical devices as well as biological applications.